Experience of COVID-19 vaccination among healthcare workers in Iran: a descriptive phenomenological study - Atefeh Torknejad; Sima Babaei; Zahra Hadian; Amir Shahzeydi (Social Determinants of Health)
Background: Healthcare professionals have been the most severely affected by the global pandemic known as COVID-19. The aim of this study was to explore the experiences and perceptions of healthcare workers in Iran regarding COVID-19 vaccination using a descriptive phenomenological approach to gain a deeper understanding of the challenges and concerns involved.